Allogeneic haematopoietic stem cell transplantation using reduced-intensity fludarabine, busulfan and anti-T lymphocyte globulin with strategic donor lymphocyte infusion in older patients with myeloid malignancy - Armstrong, Christopher; Orfali, Nina (My University, 2025)
Fludarabine, busulfan and anti-T lymphocyte globulin (FLUBU3+ATLG) reduced-intensity conditioning is an established preparative regimen for allogeneic haematopoietic stem cell transplantation in older patients with myeloid malignancy. We examined its modern-day performance in 175 sequentially-treated patients on our national programme. Overall survival was 72.4% at 2 years (95% CI 64.6-78.6%) with a cumulative incidence of non-relapse mortality of 11%. The cumulative 2-year relapse incidence was 27% (95% CI 22.8-37.6%) and was partially ameliorated by chronic graft-versus-host disease (HR 0.35, 95% CI 0.12–0.98, p=0.02). Mixed donor chimerism was observed in 51.5% beyond day 90 but relapse was significantly reduced in these patients by adopting a pre-emptive donor lymphocyte infusion (DLI) strategy (HR 0.22, 95% CI 0.07 – 0.69, p=0.005). The use of DLI as part of post-relapse salvage was also effective, with an improved median survival duration of 6 months in recipients (HR 0.43, 95% CI 0.18–0.98, p=0.01). Outcomes in patients >65 years and a limited cohort >70 years are encouraging and compare favourably to published survival results using alternate reduced-intensity regimens. FLUBU3+ATLG, supported by modern supportive care and a pre-emptive DLI strategy, is well-tolerated by older patients across a spectrum of myeloid disease with modest toxicity and favourable long-term outcomes.
ACCEPTED
Keywords: Myeloid; Allogeneic stem cell transplant; Reduced intensity conditioning; Frailty; Immune reconstitution; Cancer